INTERPERSONAL COMMUNICATION IN IMMUNIZATION (International journal of artificial intelligence, 2026)
Interpersonal communication is a vital factor in the success of immunization programs, the article under consideration stating that quality interactions between health professionals, patients, and the society at large have a positive impact on vaccination rates and, consequently, on public health. According to the findings, good interpersonal communication is an important factor in the acceptance of vaccines, overcoming hesitancy, and building the trust of the public in vaccination programs.